If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + (5x + 43) + 37 = 0 Reorder the terms: 5x + (43 + 5x) + 37 = 0 Remove parenthesis around (43 + 5x) 5x + 43 + 5x + 37 = 0 Reorder the terms: 43 + 37 + 5x + 5x = 0 Combine like terms: 43 + 37 = 80 80 + 5x + 5x = 0 Combine like terms: 5x + 5x = 10x 80 + 10x = 0 Solving 80 + 10x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-80' to each side of the equation. 80 + -80 + 10x = 0 + -80 Combine like terms: 80 + -80 = 0 0 + 10x = 0 + -80 10x = 0 + -80 Combine like terms: 0 + -80 = -80 10x = -80 Divide each side by '10'. x = -8 Simplifying x = -8
| -3.4p+5.8-(7p+0.4)+5.8p= | | y=1/3f(x) | | 10x-6=2(5x-4) | | 2y+2-y=9 | | 3x-(x+5-1)+(x-x+4)= | | f^2+3f-70= | | X^2-6x+10=o | | (w*1)+(1-w)*11=3 | | 5-y-3y=27 | | f(x)=x^2-5x-150 | | x^2=56+x | | 11x+20=15x | | 6x^2+41x-7= | | m^2+4m-60= | | 2(x+6)=x-3 | | 2y-3(4-2y)=2(y-3)+6 | | 21/44 | | 5x-9=x+19 | | 5x^3+33x^2+44x+2=-18 | | 27-2x=x^2+4x | | 7x-2/3=14 | | x^3+.6x^2-7.7x+1.4=0 | | 7m+1=m^2+13 | | y=f(x-4) | | 3(4k-1)+2(5k-3k)=7k | | 2(9y^2+12+4)=0 | | 2t-4t=4 | | -2x+21=x+9 | | 3x^4y^6+6x^5y^5= | | (49x^4)^1/2 | | 9x-2.1+.9=.2(5-x) | | 9x+20y=-50 |